Gambaran Kesiapan Mahasiswa Program Merdeka Belajar Kampus Merdeka Pada Program Studi Pendidikan Agama Islam, Universitas Al Azhar Indonesia: Studi Kasus Pertukaran Mahasiswa Merdeka Dalam Negeri - Bahrul Ulum; Tata Septayuda (Universitas Al Azhar Indonesia, 2022)
This study aims to describe the readiness of students to take part in MBKM, especially the Student Exchange Program (PMMDN) at the Islamic Education, University of Al Azhar Indonesia. This study uses a qualitative method with a case study approach that is focused on the implementation of the PMMDN program. Data analysis obtained from the Ministry of Education and Culture and the Faculty of Psychology and Education, Al-Azhar University Indonesia survey regarding MBKM were analyzed using descriptive analysis presented narratively. MBKM aims to encourage students to master various sciences and improve skills before entering the working world. In the light of the findings of this study, it can be concluded that the PMMDN program may develop leadership skills and soft skills of students who are able to interact with various backgrounds to increase unity and nationalism; providing learning experiences at other universities through a credit transfer system to strengthen and expand competencies; providing the experience of diversity through the implementation of the Nusantara module. The recommendation of this research is that the university can further increase the number of students who take part in the MBKMKeywords - The Student Exchange, MBKM, Independent Campus, PMMDN